AI Integration in Pakistan's Banking Sector: Examining the Impact on Organizational Outcomes with Employee Adaptability as a Moderator - Dr. Ali Raza Rang; Javed Ahmed Dahri; Naeem Akbar Channar; Anjum Ara (Spectrum of Engineering Sciences, 2025)
Artificial Intelligence (AI) has established itself in Pakistan’s banking domain by plunging the banks into holistic and productive AI technology, enhanced operational efficiency, better risk management and enhanced customer engagement. But for AI to work, the employee needs to be open to technological change as failure to do so would result in resistance which will negate the benefits of AI. The effect of employee adaptability in moderating the impact of AI integration on organizational outcome is investigated within this study. This research explores the usage of AI driven automation, predictive analytics and decision making tools to boost the banking performance and make a point that workforce readiness is needed. The data were collected through structured, closed ended questionnaire followed by seven point Likert type scale. A questionnaire was distributed to top level, middle level, and first line managers in all the private sector banks of Karachi, Sindh. According to statistical requirements for structural equation modeling (SEM), we set our sample size at 391 respondents informed through snowball sampling method based on carrying out the implementation of AI to banking professionals. Smart PLS was utilized to analyze the data in order to ensure robust assessment of relationships between (AI integration, organizational outcomes, and) moderating effects of (employee) adaptability. The findings show that AI adoption can greatly enhance banking efficiency and risk management but this only happens with strategic leadership in place, digital literacy programs and change management initiatives in place. Based on the insights from the findings of this study, practitioners drawn from banking institutions, policymakers, and technology providers will be equipped with practical takeaways that will help them in the success of AI acceptance as well as sustainable technological growth in the banking industry of Pakistan. Keyword: Artificial Intelligence, Employee Adoptability, Organizational outcomes, Private banking Sector.